2012
DOI: 10.1210/jc.2011-2332
|View full text |Cite
|
Sign up to set email alerts
|

Update on Bone Anabolics in Osteoporosis Treatment: Rationale, Current Status, and Perspectives

Abstract: Osteoporosis is defined as low bone mineral density associated with skeletal fractures secondary to minimal or no trauma, most often involving the spine, the hip, and the forearm. The decrease in bone mineral density is the consequence of an unbalanced bone remodeling process, with higher bone resorption than bone formation. Osteoporosis affects predominantly postmenopausal women, but also older men. This chronic disease represents a considerable medical and socioeconomic burden for modern societies. The thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
267
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(273 citation statements)
references
References 103 publications
4
267
0
2
Order By: Relevance
“…A significant drawback to the use of PTH as an osteoporosis drug is that its anabolic potency declines within a relatively short period of time, which is particularly problematic in treating a chronic degenerative disease [21]. The cellular and molecular mechanisms underlying this closing of the PTH anabolic window are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A significant drawback to the use of PTH as an osteoporosis drug is that its anabolic potency declines within a relatively short period of time, which is particularly problematic in treating a chronic degenerative disease [21]. The cellular and molecular mechanisms underlying this closing of the PTH anabolic window are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, bone anabolic therapeutics may act as an important adjunct for advanced osteoporosis to regenerate lost tissue [3,4]. Given the limited lifespan of the osteoblast [5], bone anabolism requires the continued replenishment of the exhausted osteoblast from an osteoprogenitor population [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The first human phase Ⅰ clinical trial, studying a humanized monoclonal sclerostin antibody in healthy men and postmenopausal women, showed that this new compound had effects on bone formation and resorption after a single month similar to those showed by rhPTH after 6 months, but with greater effects on bone mass than rhPTH [39] . Such data are, then confirmed, in a phase II study in more than 400 postmenopausal osteoporotic women who showed a significantly increase in BMD at the lumbar spine compared with placebo and teriparatide [40] . Antagonists to inhibitors of the Wnt pathway have show to have positive effect on osteoblast activity regardless of osteoclasts and bone resorption.…”
Section: Activin Antagonistsmentioning
confidence: 63%